2018
DOI: 10.4315/0362-028x.jfp-17-489
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Impact of Varied Carvacrol Concentrations on Salmonella Recovery in Oregano and How Corn Oil Can Minimize the Effect of Carvacrol during Preenrichment

Abstract: Phenolic compounds, like carvacrol, in oregano interfere with the detection of foodborne pathogens such as Salmonella enterica. Carvacrol concentration varies based on plant cultivars and growth region. Six oregano cultivars were used to compare the impact of carvacrol concentration on Salmonella and to evaluate the effectiveness of corn oil to help increase Salmonella survival for detection. The results of Agilent 1200 series high-performance liquid chromatography analysis showed that carvacrol concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…The antimicrobial properties of carvacrol directed against food-borne pathogens such as C. jejuni [26,29,30,37] Salmonella spp. [37,[43][44][45], Escherichia coli O157:H7 [46] and Bacillus cereus [47,48] have been shown in vitro recently. Synthetic carvacrol was, however, more effective against Gram-negative bacteria than against Gram-positive species [49].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial properties of carvacrol directed against food-borne pathogens such as C. jejuni [26,29,30,37] Salmonella spp. [37,[43][44][45], Escherichia coli O157:H7 [46] and Bacillus cereus [47,48] have been shown in vitro recently. Synthetic carvacrol was, however, more effective against Gram-negative bacteria than against Gram-positive species [49].…”
Section: Discussionmentioning
confidence: 99%
“…The synergic effects of carvacrol with thymol have the higher antibacterial and efflux pump inhibiting capacities in the case of foodborne pathogens (Miladi et al, 2016 ). Beaubrun et al ( 2018 ) showed that carvacrol exhibited antimicrobial activity against S. enterica pre‐enriched with or without 2% (v/v) corn oil.…”
Section: Therapeutic Perspectivesmentioning
confidence: 99%